(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Spruce and fir wood is important for Greek and Bulgarian forestry and wood industry. Durability of spruce and fir mature heartwood is low and both species are refractory to impregnation - spruce wood is poorly or not permeable, while fir wood is poorly to moderately permeable. The low permeability and the resistance of fir and spruce wood to impregnation are attributed to its specific anatomical – characteristics and properties. This work presents the structural characteristics and properties, summarises those anatomical characteristics which are related to impregnation processes and looks for new methods to improve fir and spruce wood permeability. Surface drilling of wood by laser beams might improve their permeability to preservatives and widen the uses of fir and spruce in exterior conditions.